1971
DOI: 10.1002/bjs.1800580716
|View full text |Cite
|
Sign up to set email alerts
|

The fate of 5-hydroxytryptamine in the lungs

Abstract: SUMMARYIsolated guinea-pig lungs perfused with Krebs solution were found to remove 5-hydroxytryptamine (5HT) from the fluid perfusing them. Two processes were involved: (I) the active uptake of 5HT by cells in the lungs, and (2) the metabolism of 5HT to 5-hydroxyindole-acetic acid (5HIAA). The experiments emphasize that the lungs have a metabolic capacity in addition to their passive function of gas diffusion.Derangement of the metabolic functions of the lungs may prove to be as serious clinically as derangeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Although our work demonstrates conclusively the existence in man of 5-HT and NE inactivation by the lung, the physiological or pathophysiological significance of the inactivation is unknown despite earlier speculation (8,(10)(11)(12). Equally unclear is the effect of increased removal of these amines, particularly in the case of NE, after total cardiopulmonary bypass.…”
Section: Amine Removal By Human Lungmentioning
confidence: 50%
See 2 more Smart Citations
“…Although our work demonstrates conclusively the existence in man of 5-HT and NE inactivation by the lung, the physiological or pathophysiological significance of the inactivation is unknown despite earlier speculation (8,(10)(11)(12). Equally unclear is the effect of increased removal of these amines, particularly in the case of NE, after total cardiopulmonary bypass.…”
Section: Amine Removal By Human Lungmentioning
confidence: 50%
“…• Both 5-hydroxytryptamine (5-HT) and norepinephrine (NE) are removed, to varying degrees, from the pulmonary vascular space of dog (1-4), cat (5), rat (6,7), guinea pig (8), and rabbit (9). Pulmonary venous and, thus, systemic arterial blood concentrations of these amines are significantly decreased by passage through the lung.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pulmonary circulation inactivates 90-95% of the bradykinin passing through it by enzymic attack without any evidence of a preliminary uptake step, and this process may be contrasted with the combined uptake and enzymic oxidation process that inactivates a comparably high proportion of 5-hydroxytryptamine passing through the pulmonary circulation (Alabaster & Bakhle, 1970;Gruby, Rowlands, Varley & Wyllie, 1971). The ability of the pulmonary circulation to inactivate two such dissimilar substances emphasizes the multiple metabolic capabilities of this vascular bed and its potential in determining the pharmacodynamics of such substances.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation occurs by a process involving carrier-mediated uptake fol lowed by metabolism to 5-hydroxyindoleacetic acid (5-H1AA) [1][2][3]. Radioauto graphic localization has confirmed that pulmonary endothelial cells are the site of serotonin uptake [4], The lung is also cap able of storing serotonin and these storage sites have been identified in neuroendo crine cells [5].…”
Section: Introductionmentioning
confidence: 99%